An analysis of the content and exercises appearing in the Fast Track Chinese Book for Non-Chinese Language Students of Phuket Rajabhat University - Saejea, Tangthao (Journal of Education Rajabhat Maha Sarakham University, 2024)
The purposes of the research were to: (1) investigate and analyze the content and exercises in the Fast Track Chinese book which used in Chinese language for general course students; (2) investigate opinions of teachers and students towards the Fast Track Chinese book, and (3) investigate guidelines for improving, developing and providing the teaching publications for students. The sample of the research consisted of 30, third year students, English for Industry Service Programme, Faculty of Humanities and Social Sciences, Phuket Rajabhat University who registered the Fundamental Chinese Language course in academic year of 2023 and 3 teachers from Chinese for Communication Programme who taught that course. The statistics used Standard Deviation, frequencies, percentage, reliability and discrimination. The research tools consisted of: (1) 3 sets of Fast Track Chinese assessment form, and (2) the samples’ opinion questionnaire. The results of the research found that: (1) the textbook consisted of content; conversation and exercises with variety activities, which was suitable for students in general course; (2) Teachers’ opinions on textbook in the aspects of content and exercises was at a high level, and the students’ opinions on textbook was at the highest level; and (3) the guidelines for developing or providing the teaching publications for students in general course with limitations on duration for learning Chinese language, content and exercises should be more interesting, focusing on the conversation with variety activities in each lesson, students could review the lessons, and the lesson could be advantage for their daily lives.